1998
DOI: 10.1108/09555349810195529
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and economic performance in the top British companies: are they linked?

Abstract: This paper investigates the relationship between corporate social responsibility (CSR) and the economic performance of corporations. It first examines the theories that suggest a relationship between the two. To test these theories, measures of CSR performance and disclosure developed by the New Consumer Group were analysed against the (past, concurrent and subsequent to CSR performance period) economic performance of 56 large UK companies. Economic performance included: financial (return on capital employed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
195
6
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(238 citation statements)
references
References 40 publications
13
195
6
11
Order By: Relevance
“…Cottrill (1990) argues that any investigation of CSR that fails to incorporate industry level realities will be fatally deficient. While Cowen, Ferreri, and Parket (1987) and Balabanis, Philips, and Lyall (1998) report that disclosure does not differ by industry type; Waddock and Graves (1997) found great difference in CSR disclosure across industries. Simpson and Kohers (2002) concentrated on the banking industry and argue that differences between industries with regard to CSR is so great that research needs to stick to just one industry.…”
Section: Industry Effectmentioning
confidence: 97%
“…Cottrill (1990) argues that any investigation of CSR that fails to incorporate industry level realities will be fatally deficient. While Cowen, Ferreri, and Parket (1987) and Balabanis, Philips, and Lyall (1998) report that disclosure does not differ by industry type; Waddock and Graves (1997) found great difference in CSR disclosure across industries. Simpson and Kohers (2002) concentrated on the banking industry and argue that differences between industries with regard to CSR is so great that research needs to stick to just one industry.…”
Section: Industry Effectmentioning
confidence: 97%
“…The following studies, among others, have found evidence for a positive relationship: Hart and Ahuja (1996), Waddock and Graves (1997), Russo and Fouts (1997), Balabanis et al (1998), Margolis and Walsh (2003), Orlitzky et al (2003), Margolis et al (2007), Montabon et al (2007), Callan and Thomas (2009), Peloza (2009), Rugman and Verbeke (2000, Porter and Linde (1995a, b), Marshall and Brown (2003), and Preston (2001). More recent studies that found positive relationship between EP and FP include Tarus (2015) for Kenya, Lin et al (2009) for Taiwan, Mishra and Suar (2010) for India, Hossain et al (2015) for Bangladesh, Lisi (2015) for Italy, and Maletič et al (2015) for multiple European countries (Germany, Poland, Serbia, Slovenia, and Spain).…”
Section: Background and Theory On Environmental Performance-firm Perfmentioning
confidence: 99%
“…It is inconclusive for findings on the relationship between CSP and CFP, existing positive relationship [6], [7]; negative relationship [8], [9]; and no relationship [10]. This study will be careful to examine their relationship with OLS model and 3SLS model.…”
Section: Relation Of Social Performance and Financial Performancementioning
confidence: 99%